ANALYSIS OF LEARNING MODEL REQUIREMENTSWRITING ACADEMIC BASED ON-LEARNING MOODLE - Oktarina, Santi; Emzir, Emzir; Rafli, Zainal (IJLECR (International Journal of Language Education and Cultural Review), 2017)
This study aims to find out how the learning model of moodle-based academic writing in Indonesian subjects required by students at Sriwijaya University in terms of students and lecturers. The method used in this study is research and development (Research and Development as proposed by Borg and Gall.Teknik data collection in the analysis of this need is a questionnaire, library review, interviews, and focus group discussion.The results show first, an instructional model of academic writing in the Moodle-based Indonesian language should refer to the Signs of Group Work Subjects Personality development in universities, the principle -The principle of learning based on KKNI, the principle of learning to write, and the principle of learning E-Learning.Second, the results showed that the shortcomings contained in the learning of academic writing in Indonesian language courses caused this lesson does not refer to Student Group Conduct Signs Personality development in universities, principles of learning based on KKNI, and the principle of learning to write maximally In addition, most lecturers do not use E-Learning learning that has been facilitated by the university. Third, the results of the study show that the learning model of academic writing in Indonesian language is needed is a learning model that applies the principles of learning in accordance with KKNI, the principles of learning to write, and the principles of E-Learning learning by adapting to the characteristics of the language courses Indonesia for college. Meanwhile, Rambu-Rambu Group Implementation Course Development of personality in universities must be adjusted in order to meet the needs of students in academic writing learning in universities.